GOR GROGOL SEBAGAI RUANG KETIGA KOTA - Gianto Purnomo; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Grogol sports center is a public facility provided by the government as a form of support for the government's concern for public health and as a place to score achievements in the field of sports. over time the GOR has unwittingly begun to be forgotten because of the declining function of the building. To revive the function of the Grogol multi sports center especially it can be utilized by the surrounding population there needs to be a new thought or concept. This sports center can be a place of social interaction for the surrounding population in addition to exercising this thought is based on the Grogol environment which is dominated by working-age population, college students and student groups. The need for open public spaces as a place of interaction for the community as well as attractive sports venues will be an attraction and a form of a new and healthy lifestyle for residents around the Grogol village. AbstrakGelanggang olahraga grogol merupakan fasilitas umum yang disediakan oleh pemerintah sebagai bentuk dukungan terhadap kepedulian pemerintah terhadap kesehatan masyarakat dan sebagai tempat untuk mencetak prestasi di bidang olahraga. seiring berlalunya waktu tanpa disadari GOR sudah mulai dilupakan karena fungsi gedung yang sudah menurun. Untuk menghidupkan kembali fungsi GOR terutama dapat dimanfaatkan oleh penduduk disekitarnya perlu ada pemikiran atau konsep baru. GOR ini dapat dijadikan tempat interaksi sosial bagi penduduk disekitarnya selain untuk berolahraga pemikiran ini didasari dari lingkungan grogol yang didominasi oleh penduduk usia kerja, mahasiswa mahasiswi maupun golongan pelajar. Kebutuhan ruang publik yang  terbuka sebagai wadah berinteraksi bagi masyarakat serta tempat olahraga yang menarik akan menjadi daya tarik dan bentuk gaya hidup yang baru dan sehat bagi penduduk disekitar kelurahan Grogol.